1977
DOI: 10.1111/j.1749-6632.1977.tb21959.x
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol Therapy of Influenza Infections of Mice and Primates With Rimantadine, Ribavirin, and Related Compounds *

Abstract: Ribavirin administered as small-article aerosols had significant therapeutic effect in the treatment of viral respiratory infections induced by influenza virus. The preliminary experiment using ribavirin to treat influenza infection in the squirrel monkey is encouraging. We expect to extend these experiments by initiating therapy at a later time to investigate the potential value of ribavirin in a clinical situation. Several derivatives of ribavirin are effective antiviral compounds. The tri-O-acetyl derivativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
18
0
1

Year Published

1981
1981
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 9 publications
0
18
0
1
Order By: Relevance
“…In previous studies, RTA has been found to be superior to ribavirin in the treatment of influenza-infected mice (12) and against arenavirus-induced hemorrhagic fever in rhesus monkeys (11). Because of its greater lipid solubility, RTA is more likely to pass through the blood-brain barrier and may act as a prodrug which is slowly hydrolyzed to ribavirin itself in vivo (2).…”
mentioning
confidence: 99%
“…In previous studies, RTA has been found to be superior to ribavirin in the treatment of influenza-infected mice (12) and against arenavirus-induced hemorrhagic fever in rhesus monkeys (11). Because of its greater lipid solubility, RTA is more likely to pass through the blood-brain barrier and may act as a prodrug which is slowly hydrolyzed to ribavirin itself in vivo (2).…”
mentioning
confidence: 99%
“…Thus, all three or any one of the foregoing mechanisms may be operational at any one time, depending on the virus infection. This potential for inhibition at more than one site may explain the failure to detect viral isolates resistant to ribavirin (15,47 (48), and parainfluenza (Sendai) virus (25); cotton rats infected with the Long strain of RSV (17); and monkeys infected with influenza A/Aichi/2/68 virus (40) and Lassa fever virus (18,19). Small-particle aerosol administration of ribavirin to mice infected with influenza A or B virus was shown to be more effective than intraperitoneal treatment (39,45,48 The use of ribavirin in a small-particle aerosol has been evaluated in double-blind, placebo-controlled studies of influenza infections in college students (lla) and in RSV infections of infants with and without complications (15,44 In 1981, ribavirin aerosol was used in the treatment of RSV infections in infants.…”
Section: Introductionmentioning
confidence: 99%
“…In recent work, ribavirin was highly effective for the treatment of influenza type A infections in animals when administered therapeutically as small-particle aerosols (SPAs) (8,9,12). This report describes the therapeutic efficacy of ribavirin given as a SPA to mice infected with a lethal respiratory dose of Sendai virus.…”
mentioning
confidence: 99%
“…The methods used for challenging mice with infectious virus and the procedures for continuous aerosol therapy have been described previously (8,9). In the ribavirin studies, the concentration of drug in the spray suspension was adjusted to yield an effective, retained aerosol dose of 50 mg of ribavirin per kg (mouse weight) per day or 100 mg/kg in 48 h of treatment.…”
mentioning
confidence: 99%